Project and Management Monitoring System Survey Drawing Inventory Unit Survey Production Tools in PT Telkom Akses Samarinda - Siti Qomariah; Basrie (Politeknik Pertanian Negeri Samarinda, 2020)
Project Monitoring System and Production Equipment Management Survey Drawing Inventory Unit at PT Telkom Samarinda Access is a system intended for SDI units because SDI units are directly related to the project and production equipment of the Telkom Group. Where on this system has several users based on their level. This system was built because so far, the system applied was still quite manual, namely a collection of online spreadsheets on Google Drive, where files with each other were still not connected so that when there was a change, not all data was connected even though the data was related. Also, the advantage of this system is that management can directly monitor a project from the Optical Distribution Point (ODP) booking process to the ODP that can be sold in the field. Project Monitoring System and Production Equipment Management Survey Unit Inventory Survey Unit PT Telkom Samarinda access was developed with Waterfall system development methods, data collection methods by interviewing, observing and studying literature, analyzing system design using UML (Unified Modeling Language). The method of testing the Monitoring System and Inventory Equipment Production uses the Blackbox testing method. With this system of monitoring and inventory of production equipment, the performance of the SDI unit as the Administrator is faster because all this time the inventory processing process is still utilizing the number of online spreadsheet files on Google Drive, while with this system all work has been systemized. Fast data search without having to open existing spreadsheet files and